Composition Engineering of Indium Zinc Oxide Semiconductors for Damage-Free Back-Channel Wet Etching Metallization of Oxide Thin-Film Transistors - Xuan Zhang; Sung Woon Cho (Micromachines, 2023)
In contrast to lift-off and shadow mask processes, the back-channel wet etching (BCWE) process is suitable for industrial-scale metallization processes for the large-area and mass production of oxide thin-film transistors (TFTs). However, chemical attacks caused by the corrosive metal etchants used in the BCWE process cause unintended performance degradation of oxide semiconductors, making it difficult to implement oxide TFT circuits through industrial-scale metallization processes. Herein, we propose composition engineering of oxide semiconductors to enhance the chemical durability and electrical stability of oxide semiconductors. The chemical durability of InZnO against Al etchants can be improved by increasing the content of indium oxide, which has a higher chemical resistance than zinc oxide. As a result, A damage-free BCWE-based metallization process was successfully demonstrated for oxide TFTs using In-rich InZnO semiconductors. Furthermore, In-rich InZnO TFTs with wet-etched Al electrodes exhibited electrical performance comparable to that of lift-off Al electrodes, without chemical attack issues.